Nitric oxide releases Cl− from acidic organelles in retinal amacrine cells - Krishnan, Vijai; Gleason, Evanna (Frontiers in Cellular Neuroscience, 2015)
Determining the factors regulating cytosolic Cl- in neurons is fundamental to our understanding of the function of GABA- and glycinergic synapses. This is because the Cl- distribution across the postsynaptic plasma membrane determines the sign and strength of postsynaptic voltage responses. We have previously demonstrated that nitric oxide (NO) releases Cl- into the cytosol from an internal compartment in both retinal amacrine cells and hippocampal neurons. Furthermore, we have shown that the increase in cytosolic Cl- is dependent upon a decrease in cytosolic pH. Here, our goals were to confirm the compartmental nature of the internal Cl- store and to test the hypothesis that Cl- is being released from acidic organelles such as the Golgi, endosomes or lysosomes. To achieve this, we made whole cell voltage clamp recordings from cultured chick retinal amacrine cells and used GABA-gated currents to track changes in cytosolic Cl-. Our results demonstrate that intact internal proton gradients are required for the NO-dependent release of internal Cl-. Furthermore, we demonstrate that increasing the pH of acidic organelles leads to release of Cl- into the cytosol. Intriguingly, the elevation of organellar pH results in a reversal in the effects of NO. These results demonstrate that cytosolic Cl- is closely linked to the regulation and maintenance of organellar pH and provide evidence that acidic compartments are the target of NO.